2013
DOI: 10.1542/peds.2012-3892
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Timing, Outpatient Follow-up, and Home Care of Late-Preterm and Early-Term Infants

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Infants born late-preterm and early-term are at higher risk of morbidity and mortality compared with term infants. Home care practices recommended for all infants include supine sleep position, no smoke exposure, and breastfeeding to optimize health outcomes. WHAT THIS STUDY ADDS:Our study provides new findings on the timing of hospital discharge, outpatient follow-up, and home care of late-preterm and early-term infants compared with term infants in the United States. abstract OB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 23 publications
3
77
0
3
Order By: Relevance
“…The researchers also found that LPIs are less likely to be discharged home exclusively breastfeeding (OR = 0.4, p = .04). These findings are supported by the work of Hwang et al () who found LPIs are less likely than term infants to initiate breastfeeding ( n = 242,471; OR = .95; p < .01). These researchers also found that LPIs have lower rates of continued breastfeeding (defined as continued breastfeeding to at least 10 weeks).…”
Section: Resultssupporting
confidence: 79%
“…The researchers also found that LPIs are less likely to be discharged home exclusively breastfeeding (OR = 0.4, p = .04). These findings are supported by the work of Hwang et al () who found LPIs are less likely than term infants to initiate breastfeeding ( n = 242,471; OR = .95; p < .01). These researchers also found that LPIs have lower rates of continued breastfeeding (defined as continued breastfeeding to at least 10 weeks).…”
Section: Resultssupporting
confidence: 79%
“…3 Although greater attention and tailored management is being implemented for late preterm infants, 4-5 late preterm birth is associated with lower rates of breastfeeding, earlier breastfeeding cessation, and more infant feeding-related morbidities than term birth. 6-11 The discrepancy in breastfeeding outcomes include those who prenatally reported intent to breastfeed. 12 Exclusive breastfeeding for 6 months and continued breastfeeding for 2 years or beyond is recommended for optimal infant nutrition and development.…”
Section: Background and Significancementioning
confidence: 99%
“…Family members can help reduce stress related to caring for LBW infant at home. Family empowerment improves parents' ability to care the infant and affects infants's health (Browne and Talmi, 2005;Hwang et al, 2013;Melnyk et al, 2009;Rustina et al, 2014). As part of the discharge planning process, nurses should assess how family support can be used to meet the needs of infants and mothers.…”
Section: Discussionmentioning
confidence: 99%